The Economy Nexus of the COVID-19 Pandemic - Mugano, Gift (Sociološki pregled, 2020)
The COVID-19 pandemic, which is unprecedented in human history and has to date resulted in 15.8 million confirmed cases with 640,016 deaths, has seen governments undertaking strict lockdown measures which not only affected local business activities but also disrupted global value chains resulting in massive economic implications. The purpose of this paper is to review the impact of the COVID-19 pandemic on the economy with a special focus on the African continent. Because the coronavirus pandemic is still evolving and its duration is uncertain, it is difficult to accurately quantify the economic implications of the pandemic. As a result, this paper used the scenario basis analysis as well as extensive literature on the subject. The results show that the pandemic, although it has devastating social impacts due to loss of human life, it has also presented serious economic challenges which inter alia include economic recession, reduced trade volumes and subdued financial flows. Because of globalisation, Africa is not immune to these challenges. As noted in this paper, major economic activities and sources of foreign exchange in Africa such as the tourism sector, export of commodities, external finances and local business activities were negatively affected, resulting in most African economies falling into recession which has wiped out economic gains of the last ten years as noted by the International Monetary Fund. In mitigating this pandemic, African countries should use incentive packages to save businesses as well as institute a number of fiscal measures such as tax waivers and engage international development partners for bail out.